1993
DOI: 10.1002/pola.1993.080311118
|View full text |Cite
|
Sign up to set email alerts
|

Ionic‐conductivity switching of vinyl malachite green leuconitrile copolymers based on photoinduced carrier generation

Abstract: SYNOPSISCopolymers of bis [ 4- ( N,N-dimethylamino ) phenyl] -4-vinylphenylmethanenitrile (vinyl Malachite Green leuconitrile) with methyl methacrylate or w-methoxyoligo (oxyethylene ) methacrylate have been synthesized, aiming a t designing one-component-type organic polymers for photoswitchable ion-conducting films. The triphenylmethanenitrile copolymers with w-methoxyoligo ( oxyethylene ) methacrylate were found to undergo ionic-conductivity switching by turning on and off UV light a t ambient temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Among these TAM derivatives, leuconitriles have attracted considerable attention owing to their applications in photoswitching materials [33,34]. The reactivity of our TAM complexes with cyanide ion is an indication of the cationic character of the central carbon atom, a character which is inherent to TAM dyes.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Among these TAM derivatives, leuconitriles have attracted considerable attention owing to their applications in photoswitching materials [33,34]. The reactivity of our TAM complexes with cyanide ion is an indication of the cationic character of the central carbon atom, a character which is inherent to TAM dyes.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Upon UV irradiation, the nonionic transparent triphenylmethane groups dissociate into ion pairs with the formation of green-colored triphenylmethyl cations; this includes dramatic changes in its optical property and hydrophobicity [21]. The ionized triphenylmethyl cation is stable at low pH and thermally photo-isomerized back to the neutral form at high pH or under dark condition [22]. Polyelectrolyte multilayer (PEM) membranes possess a unique suitability for salt and gas separations [23,24], pervaporation [25,26] of water/organic solvent mixtures and reverse osmosis membranes [27,28], because they provide control on film thickness on the nanometer scale.…”
Section: Introductionmentioning
confidence: 98%
“…We had designed ion-conducting polymers containing a Malachite Green dye moiety whose ionic conductivities are photochemically switchable by a photoinduced carrier-generation mechanism. One-component-type ion-conducting polymers carrying a Malachite Green leuconitrile moiety, that is, copolymers of a Malachite Green leuconitrile vinyl monomer with a methacrylate-type monomer, were synthesized as a convenient material for photoresponsive ionic conduction . A unique type of photochemical cation complexation control system can be also designed by providing Malachite Green dyes with a crown ether moiety.…”
Section: Introductionmentioning
confidence: 99%
“…One-component-type ionconducting polymers carrying a Malachite Green leuconitrile moiety, that is, copolymers of a Malachite Green leuconitrile vinyl monomer with a methacrylate-type monomer, were synthesized as a convenient material for photoresponsive ionic conduction. 6 A unique type of photochemical cation complexation control system can be also designed by providing Malachite Green dyes with a crown ether moiety. We already reported that in a Malachite Green leuconitrile carrying a crown ether moiety, so-called crowned Malachite Green, the metal ion complexation of its crown ether moiety can be controlled photochemically, based on electrostatic repulsion between the triphenylmethyl cation and a metal ion complexed by its crown moiety.…”
Section: Introductionmentioning
confidence: 99%